Art of scenic design : a practical guide to the creative process - Morgan, Robert Mark (London [England] : Bloomsbury Methuen Drama, 2022)
"How do you navigate a career as an entertainment designer while maintaining a sense of self-worth and value in the various off-ramps and sidestreets you may choose to take on the journey? The Art of Scenic Design provides an in-depth look at the scenic design process for young designers as well as creative entrepreneurs seeking to nurture a collaborative environment that leads to rediscovery and innovation in their work. Based on his 30 years of experience in stage design, exhibit design, art direction for film, and theme park and industrial design, Robert Mark Morgan demonstrates that while a design process for creating these types of works can seem like niche professions, the lessons learned in collaboration, testing and re-testing ideas, prototyping concepts, overcoming fears, venturing guesses, divergent thinking, and the creative process in general are applicable - and valuable - in nearly all disciplines and professions both inside and outside of the entertainment industry. In The Art of Scenic Design: A Practical Guide to the Creative Process you will follow an accomplished designer on a narrative of the theatrical design process from early phases of a design with a creative team encompassing visual research, idea-making, and collaborative relationships, to sketching, prototyping, and testing ideas, through to the execution and manifestation of the design with a team of artisans. The design journey is contextualized with backstage stories of 'what if?' moments, provocative discussions, and lessons that are indispensable to your professional development"--
List of Figures -- Foreword -- Acknowledgements -- Introduction: "And Just Like That" -- Chapter One: The Designer as a Child Futurist -- Chapter Two: Empathy and Answering "What Story Are We Telling" with Collaborators -- Chapter Three: The Importance of Research as "Fuel" for ANY Process -- Chapter Four: Clawing and Scratching Out an Idea -- Chapter Five: Modeling and Shaping an Object and an Idea -- Chapter Six: Creative Swings, Career Fields, and Collaboration -- Chapter Seven: The Tech and Preview Process - the Ultimate Proof-of-Concept -- Chapter Eight: The Inevitability of Failure and the Sea of Criticism -- Chapter Nine: Where Do We Go From Here? -- References -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Theaters -- Stage-setting and scenery; Theatre: technical & background skills,Product design,Careers guidance,Other performing arts; Electronic books